Hadis Tentang Mengeraskan Suara: Kajian Ma’anil Hadis dengan Pendekatan al-Wasilah al-Mutaghayyirah wa al-Hadf al-Thabit Perspektif Yusuf al-Qardhawi - Muhid, Muhid; Shofa, Zumrotus; Suryani, Khotimah (UIN Syarif Hidayatullah Jakarta, 2024)
Zikr is a form of worship that is light but has great rewards that is said through the heart and verbally, dhikr is also a worship that essentially means a person is connecting with Allah. Therefore, this research explains the hadith of raising one's voice in the principles of Al-Wasilah al-Mutaghayyirah wa al-Hadf al-Thabit, views of Yusuf al-Qardhawi. The research used by the author is qualitative research using the library research method. The results of the author's research show that the behavior of raising one's voice when doing dhikr is permissible, as long as it does not disturb other congregation members in the surrounding area. Returning to the rule that Yusuf al-Qardhawi uses, the means can change according to situations and conditions, but do not change the original goals set at the beginning. Dhikr can be done using any means, including by raising your voice, lowering your voice, lying down, sitting, sleeping, walking, standing and so on with the intention of not just showing off for Allah's sake in front of other people. In this case, as a Muslim, it would be better not to arbitrarily blame other people, even if they have different beliefs.